Changes of liver metabolites following hepatectomy with ischemia reperfusion towards liver regeneration. Issue 3 (30th January 2018) - Saito, Yu; Morine, Yuji; Iwahashi, Shuichi; Ikemoto, Tetsuya; Imura, Satoru; Yamanaka‐Okumura, Hisami; Hirayama, Akiyoshi; Soga, Tomoyoshi; Tomita, Masaru; Shimada, Mitsuo
Abstract: Background: Metabolome analysis is one of the omics which investigates the final product of a central dogma. Changes of liver metabolites during liver regeneration following hepatectomy (Hx) continue to remain unclear. The aim of the present study was to investigate the changes of liver metabolites following Hx with ischemia reperfusion (I/R) towards liver regeneration. Methods: Twenty‐three patients who underwent Hx were enrolled in this study. Non‐tumor tissues were sampled immediately before and after Hx and a comparison was made between the liver samples taken before and after Hx using capillary electrophoresis (CE)—time‐of‐flight mass spectrometry (TOFMS) as metabolome analysis. Results: The metabolic pathway showed that there was a significant increase in "lactate" following Hx. There was a significant decrease in metabolites only in the first half of the tricarboxylic acid cycle (TCA) cycle, and adenosine triphosphate (ATP) by anaerobiotic glycolysis did not occur in time for energy consumption of the Hx. Principal component analysis revealed remarkably different component profiles between the samples taken before and after Hx. One hundred and three metabolites were selected as critical metabolites for separating components. Valine and tryptophan increased significantly after Hx and they were regulated by resected liver volume, ischemic time and liver function. Conclusion: The liver metabolites changed remarkably between before and after Hx. Especially, liver valine and tryptophan were increased. Abstract : We investigated the changes of liver metabolites following hepatectomy (Hx) with ischemia reperfusion (I/R) towards liver regeneration using metabolome analysis.